Embryonic Thermal Manipulation Affects Body Performance Parameters and Cecum Microbiome in Broiler Chickens in Response to Post-Hatch Chronic Heat Stress Challenge - Rahmeh Dahadha; Seif Hundam; Mohammad Borhan Al-Zghoul; Lo’ai Alanagreh; Mustafa Ababneh; Mohammad Mayyas; Daoud Alghizzawi; Minas A. Mustafa; David E. Gerrard; Rami A. Dalloul (Animals)
Rising global temperatures challenge poultry production by disrupting the cecal microbiota, which is essential for chicken health. Thermal manipulation (TM) during embryogenesis is a potential strategy to enhance thermotolerance in broilers. This study examined TM’s effects on the cecal microbiome, body weight (BW), and body temperature (BT) under chronic heat stress (CHS). Fertile Indian River eggs (n = 800) were incubated under control (37.8 °C, 56% RH) or TM conditions (39 °C, 65% RH for 18 h per day from embryonic day 10 to 18). On post-hatch day 18, male chicks were assigned to either CHS (35 ± 0.5 °C for five days) or thermoneutral conditions (24 ± 0.5 °C). The CHS-TM group showed a significantly higher BW than the CHS-CON group (p < 0.05). Under thermoneutral conditions, TM chicks had a lower BT on day 1 (p < 0.05), while the CHS-TM group exhibited a non-significant BT reduction compared to the CHS-CON group under heat stress (p > 0.05). An analysis of the gut microbiome showed that the beta diversity analysis (PERMANOVA, p < 0.05) indicated distinct microbial shifts. Firmicutes and Bacteroidota dominated the phylum level, with CHS increased Bacilli and Lactobacillus while reducing Lachnospirales in the CHS-TM group. These findings suggest that TM modulates gut microbiota and mitigates BW loss, offering a potential strategy to enhance broilers’ resilience to heat stress.